Organisational Communication in Islamic Education: A Case Study of Madrasah Aliyah Salafiyah Cirebon - Ramadhan, Mohamad Azis; Sadat, Fahad Achmad (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
Abstract: This study provides an in-depth analysis of organisational communication within Islamic education, focusing on Madrasah Aliyah (MA) Salafiyah Cirebon. Employing a qualitative case study approach, the research integrates triangulation methods, including interviews, observations, and document analysis, to explore the educational communication processes and challenges at MA Salafiyah. Data were collected over two months, involving purposive sampling of key participants such as the Principal, Vice Principal of Curriculum, teachers, students, and administrative staff. The findings reveal a complex network of formal and informal communication channels among school leaders, educators, students, parents, alumni, and external stakeholders, emphasising their critical role in school operations and community building. Despite effective internal communication dynamics, psychological, physical, cultural, and environmental barriers were identified. The study underscores the importance of utilising diverse communication media to mitigate these barriers, with significant implications for enhancing the quality of Islamic education. Continuous evaluation and adaptation of communication practices and active stakeholder involvement are essential for achieving educational excellence. However, the study's focus on a single institution limits the generalizability of the findings, indicating the need for broader research across various educational settings. Future studies should incorporate quantitative analyses to complement the qualitative data and examine the impact of specific interventions on educational outcomes. Abstrak: Penelitian ini memberikan analisis mendalam tentang komunikasi organisasi dalam pendidikan Islam, dengan fokus pada Madrasah Aliyah (MA) Salafiyah Cirebon. Menggunakan pendekatan studi kasus kualitatif, penelitian ini mengintegrasikan metode triangulasi, termasuk wawancara, observasi, dan analisis dokumen, untuk mengeksplorasi proses komunikasi pendidikan dan tantangan yang ada di MA Salafiyah. Data dikumpulkan selama dua bulan, melibatkan purposive sampling dari peserta kunci seperti Kepala Sekolah, Wakil Kepala Kurikulum, guru, siswa, dan staf administrasi. Temuan mengungkapkan jaringan komunikasi formal dan informal yang kompleks di antara pimpinan sekolah, pendidik, siswa, orang tua, alumni, dan pemangku kepentingan eksternal, yang menekankan peran kritis mereka dalam operasi sekolah dan pembangunan komunitas. Meskipun dinamika komunikasi internal efektif, terdapat hambatan seperti faktor psikologis, fisik, budaya, dan lingkungan. Studi ini menekankan pentingnya menggunakan berbagai media komunikasi untuk mengatasi hambatan tersebut, dengan implikasi signifikan untuk meningkatkan kualitas pendidikan Islam. Evaluasi dan adaptasi berkelanjutan dari praktik komunikasi, bersama dengan keterlibatan aktif pemangku kepentingan, sangat penting untuk mencapai keunggulan pendidikan. Namun, fokus studi pada satu institusi membatasi generalisasi temuan, menunjukkan perlunya penelitian yang lebih luas di berbagai lingkungan pendidikan. Studi masa depan harus menggabungkan analisis kuantitatif untuk melengkapi data kualitatif dan meneliti dampak intervensi spesifik pada hasil pendidikan.